A Qualitative Investigation of Gerontological Practice: The Views of Social Work and Psychology Students, Faculty, and Practitioners. Issue 4 (1st October 2016) - Webb, Stephanie; Chonody, Jill; Ranzijn, Rob; Bryan, Janet; Owen, Mikaela
Abstract : Recently there has been an increase in the population of older adults; however, this increase has not been reflected in the helping professions. The aim of this study was to qualitatively investigate barriers to working with older adults within the human service professions. An online survey was sent to students, academic faculty, and practitioners from the disciplines of social work and psychology throughout Australia, addressing issues related to work with older adults. Thematic analysis was used to extract themes and subthemes from the responses ( N = 252). The most important finding was that a barrier to working with older adults appears to be a consequence of a perpetuating cycle among students, academic faculty, and professionals collectively. Faculty members did not feel knowledgeable in the area of gerontology and were therefore not able to educate students in this area appropriately, leading to students to enter the workforce as either faculty members and/or practitioners without expertise to work with older adults. This study highlighted the importance of including more comprehensive gerontological information within social sciences' curriculum, which may promote more realistic images of older adults and help alleviate barriers to working with this population.